The Legend of the Great Inquisitor as the Anti-Utopian pioneering work and the novel "We": by Russian writer Yevgeny Ivanovich Zamyatin - KOBAISH, MOHAMMED FRAYYEH (Al-Adab Journal, 2019)
In the research given to the example of the great Inquisitor’s legend, the latest novel by the Great Russian writer Fyodor Mikhailovich Dostoevsky, "The Brothers Karamazov" confirms the idea of ​​man’s loss of utopian ideas in its own right, and the forced loss of human happiness to the utopian society. The researcher compared this millennium to the great writer Fyodor Mikhailovich Dostoevsky in another recent production, the novel by the Russian writer Yevgeny Ivanovich Zamyatin "we" as the author confirms the idea of ​​the myth that concludes the novel " The Brothers Karamazov" all Russian anti-utopian works.